This was not a comic : a critical and creative investigation into the narrative strengths of comics presented in fulfilment of the requirements for the degree of Masters in Creative Writing at Massey University, Albany, Aotearoa - Black, Tara Elizabeth (Massey University, 2018)
Comics can be a difficult medium to classify. They come in so many shapes and sizes: strip cartoons, separate issues of superhero comics, and even the stand-alone, book-length narratives which have come to be called ‘graphic novels.’ The critical component of this MCW thesis does not seek so much to classify comics as to look at the narrative strengths of the medium through the lens of their influence on the author, in particular, as both a comics consumer and creator. The particular combination of words and pictures in sequence that characterises comics has the power to play with an audience’s sense of time, visual metaphor, and reality through repetition and closure. It is these three aspects of the form that both the critical (roughly 30%) and creative (70%) components of this Masters of Creative writing seek to explore. The creative component of this MCW is a graphic novel in the style of a diary comic called This Is Not a Pipe. It explores how visual metaphor and repetition in comics can complicate the reader’s sense of the reality of the narrative. It is highly recommended that you read this work first for the exegesis in the critical essay to make sense. The critical component, ‘This Was Not a Comic’ is in two parts. The first half analyses Bill Watterson’s Calvin and Hobbes, Dylan Horrock’s Hicksville, and Eleanor Davis’s You & a Bike & a Road in order to identify certain of the specific narrative qualities of comics. The second part is an explanation of how This Is Not a Pipe actually became a comic, rather than the novel it was originally intended to be, and the creative consequences of this decision.
Keywords: Graphic novels; Comic books, strips, etc; Criticism and interpretation; Black, Tara, 1984-; This is not a pipe; Watterson, Bill; Calvin and Hobbes; Horrocks, Dylan; Hicksville; Davis, Eleanor, 1983-; You & a bike & a road; 360201 Creative writing (incl. scriptwriting)